2015
DOI: 10.1007/s12098-015-1952-7
|View full text |Cite
|
Sign up to set email alerts
|

Early House Dust Mite Sensitivity in Mumbai Children

Abstract: Children in Mumbai show early sensitization to HDM. D. pteronyssinus is the commonest offending allergen in the index study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
4
7
0
Order By: Relevance
“…These findings might be attributable to the natural history of atopic disorders (atopic march) where exposure to outdoor allergens occurring in later childhood. This is similar to the observation by Al-Zayadneh et al who reported SPT positivity increasing significantly with age [19,23]. Aeroallergen sensitization in wheezing children (n=100) was studied by Pendino et al and found sensitization to dust mite, pollen, and mold to be 58%, 13%, and 8% respectively [24].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings might be attributable to the natural history of atopic disorders (atopic march) where exposure to outdoor allergens occurring in later childhood. This is similar to the observation by Al-Zayadneh et al who reported SPT positivity increasing significantly with age [19,23]. Aeroallergen sensitization in wheezing children (n=100) was studied by Pendino et al and found sensitization to dust mite, pollen, and mold to be 58%, 13%, and 8% respectively [24].…”
Section: Discussionsupporting
confidence: 87%
“…D. pteronyssinus and D. farinae are the two predominant mites tested in the present study with a positivity rate of 22.5% and 21.3%, respectively. Doshi and Tripathi and Al-Zayadneh et al reported the most predominant mite to be D. pteronyssinus similar to our study [19,23]. However, Luo et al reported significantly high positivity in SPT for D. farinae as compared to D. pteronyssinus (50.0% vs. 14.7%; P<0.05) [20].…”
Section: Discussionsupporting
confidence: 85%
“…It has also been concluded that the most common cause of sensitization in allergic patients was D. pteronyssinus mite followed by D. farinae, D. microceras and D. aureliani. The above findings are in accordance with the findings of Sun et al (2014), Doshi and Tripathi (2016) and Miller (2018). Study done by Miller (2018) showed that house dust mites are the main cause of atopic sensitization and allergic disorders throughout the world.…”
Section: B Composition Of Identified Mite Faunasupporting
confidence: 90%
“…Aeroallergen sensitization patterns in atopic individuals in various Asian countries, namely China, Hong Kong, India, Japan, Korea, Malaysia, Philippines, Singapore, Taiwan, Thailand and Vietnam are shown in the Table 1 and Figure 1. 5,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] No published data from Myanmar, Laos and Cambodia were available. Studies involving aeroallergen distribution alone without human sensitization, and those involving sensitization without associated atopy were not included.…”
Section: Aeroallergen Sensitization Patterns In Asian Countriesmentioning
confidence: 99%